The vicious circle of stereotypes: Teachers' awareness of and responses to students' gender-stereotypical behaviour. - Aleksandra Gajda; Agnieszka Bójko; Ewa Stoecker (PLoS ONE, 2022)
The study was conducted using a mixed methods approach combining lesson observations and interviews with teachers. A total of 204 hours of observation in 34 classes of 7th and 8th graders (aged 13-14 in the Polish primary school system) were conducted to investigate teachers' behaviour that may exacerbate gender stereotypes and gender bias in the classroom. Moreover, the 25 female teachers conducting the observed lessons were interviewed to identify: (i) teachers' awareness of stereotypical behaviours of girls and boys during classes; (ii) teachers' awareness of possible causes of these behaviours; (iii) teachers' responses to these behaviours, including actions that could deepen gender stereotypes; and (iv) teachers' sensitivity to the gender polarised content of school textbooks. The results of the study show that teachers, although they are aware of the existence of gender stereotypes and declare their willingness to counteract them, tend to strengthen rather than eliminate these stereotypes with the strategies and actions undertaken. They have difficulty recognising possible reasons for the occurrence of stereotypical student behaviour and have little awareness of the gender-polarised content of school textbooks. The results of the study are discussed, inter alia, in light of the concept of the vicious circle of stereotypes and self-fulfilling prophecies in education.